High methanol‐to‐formate ratios induce butanol production in Eubacterium limosum - Jamin C. Wood (Microbial Biotechnology, 2022)
Summary Unlike gaseous C1 feedstocks for acetogenic bacteria, there has been less attention on liquid C1 feedstocks, despite benefits in terms of energy efficiency, mass transfer and integration within existing fermentation infrastructure. Here, we present growth of Eubacterium limosum ATCC8486 using methanol and formate as substrates, finding evidence for the first time of native butanol production. We varied ratios of methanol‐to‐formate in batch serum bottle fermentations, showing butyrate is the major product (maximum specific rate 220 ± 23 mmol‐C gDCW‐1day‐1). Increasing this ratio showed methanol is the key feedstock driving the product spectrum towards more reduced products, such as butanol (maximum titre 2.0 ± 1.1 mM‐C). However, both substrates are required for a high growth rate (maximum 0.19 ± 0.011 h‐1) and cell density (maximum 1.2 ± 0.043 gDCW l‐1), with formate being the preferred substrate. In fact, formate and methanol are consumed in two distinct growth phases – growth phase 1, on predominately formate and growth phase 2 on methanol, which must balance. Because the second growth varied according to the first growth on formate, this suggests butanol production is due to overflow metabolism, similar to 2,3‐butanediol production in other acetogens. However, further research is required to confirm the butanol production pathway in E. limosum, particularly given, unlike other substrates, methanol likely results in mostly NADH generation, not reduced ferredoxin.